Unleashing the power of AI open platforms to revolutionize research process / Nur Dalila Khirul Ashar - Khirul Ashar, Nur Dalila (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
Artificial Intelligence (AI) has emerged as one of the most transformative technologies in recent years, with ground-breaking innovations like OpenAI and ChatGPT taking things to a whole new level. Based on generative AI technology built on a large language model (LLM), it has already demonstrated promising results in various application areas, including content generation, natural language processing, virtual assistants, recommendation systems, and interactive media. The rapid advancement of technology has led to an exponential increase in research outputs. There are potentials in changing the ways research are conducted, as there has been a recent surge in new AI-powered tools that could assist researchers in their works by helping them write, interpret, and analyse data. While some researchers are sceptical about the quality and originality of AI-generated texts, others welcome these tools as means to increase productivity while reducing the time and cost of manuscript production. These technologies have the potentials to significantly accelerate scientific discoveries and lead to breakthroughs by opening new avenues for scientific research. Another benefit of open AI platforms is hat they encourage collaboration and information sharing, allowing scientists to focus on solving complex problems and expanding knowledge in their field. These platforms enable academics to share data, models, and tools, leading to a vibrant community of scientists and practitioners working together to solve difficult problems. This allows new ideas to be developed, gaps in knowledge to be identified, and the boundaries of their respective professions to be pushed. Significant advances could be achieved in research and development, as well as new discoveries and advances that were not previously feasible.